Growth Strategy of Malay Entrepreneurs - Challenges and Opportunities: A Malaysian Case - Ummi Salwa Ahmad Bustamam (2024)
This paper has been presented at the Asian Business & Management Conference, 10th October 2010, in Osaka, Japan.